Architectural Valorization: Lighting Design Solution for the Bell Tower of "San Pasquale a Chiaia" Church. Issue 2 (November 2021) - Iuliano, Giuseppina; Spanodimitriou, Yorgos; Ciampi, Giovanni; Scorpio, Michelangelo; Sibilio, Sergio
Abstract: Christian churches and their bell towers represent a big part of the historical architectural heritage in Italy, and they had a major role in the development of the urban and social fabric of the Italian cities. This study is focused on the design of a lighting renovation for the bell tower of "San Pasquale a Chiaia" (Napoli, south of Italy). The lighting refurbishment is designed with the aim of: (i) emphasizing the architecture of the bell tower façades and (ii) providing a figurative and emotional role to the whole building. Several lighting scenarios have been implemented in order to compare the different luminaire types and arrangements on the basis of the effectiveness in valorizing the architectural characteristics of the bell tower, as well as the energy performances of the different design solutions. Finally, the best case has been further implemented in order to take into account the different needs of the historical building as well as the enhancement of the surrounding urban spaces.